Implementation of a Mandatory Will for Children Who Do Not Have Legality From Religious Court - Jakaria Puntodewo; Farida Nurun Nazah (ADP Publisher, 2024)
The inheritance distribution for adopted children without official legal recognition from the Religious Court often leads to disputes, particularly among legitimate heirs. This study aims to analyze and understand the implementation of inheritance processes for adopted children who have not obtained formal legal status. Referring to the Compilation of Islamic Law, this research employs a normative qualitative method with a case study approach to explore the application of the testamentary obligatory mechanism. The findings reveal that the testament obligatory mechanism can be used to allocate inheritance to adopted children who lack nasabiyah (bloodline) or sababiyah (marital ties) relationships. This obligatory bequest serves as a fair legal solution to accommodate the interests of adopted children while adhering to Islamic legal principles and minimizing potential disputes among legitimate heirs.